2019
DOI: 10.1038/s41390-019-0514-5
|View full text |Cite
|
Sign up to set email alerts
|

Very preterm neonates receiving “aggressive” nutrition and early nCPAP had similar long-term respiratory outcomes as term neonates

Abstract: BackroundThe impact of the consistent implementation of “aggressive” nutrition by means of intensive early neonatal nutritional support up to 40–44 weeks postmenstrual age and the use of nasal continuous positive airway pressure (nCPAP) within the first hour of life on the respiratory function of very premature neonates (VPN) at school age is unclear.MethodRespiratory function was evaluated in 108 VPN and 70 term controls. Growth, frequency of lower respiratory tract infections, re-hospitalization, and spirome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Postnatal growth restriction is common with very premature birth and increases the risk of BPD and PH. Retrospective cohort studies have demonstrated associations between decreased caloric intake in the first weeks of life and BPD in very preterm infants (6,7,23), and limited studies of aggressive nutrition in the first weeks of life have shown benefit in decreasing BPD in this same population (24). NEC is also a risk factor for PH in very preterm infants both with and without BPD (9), supporting the hypothesis that inflammation in the gut impacts the developing lung vasculature.…”
Section: Discussionmentioning
confidence: 98%
“…Postnatal growth restriction is common with very premature birth and increases the risk of BPD and PH. Retrospective cohort studies have demonstrated associations between decreased caloric intake in the first weeks of life and BPD in very preterm infants (6,7,23), and limited studies of aggressive nutrition in the first weeks of life have shown benefit in decreasing BPD in this same population (24). NEC is also a risk factor for PH in very preterm infants both with and without BPD (9), supporting the hypothesis that inflammation in the gut impacts the developing lung vasculature.…”
Section: Discussionmentioning
confidence: 98%
“…Even though improvement of postnatal growth and identification of risk factors was one of our aims, the major focus of our paper was to reflect on how different approaches to analyzing postnatal growth can result into confusing and even inaccurate conclusions. Current reported percentages of EUGR are indeed heterogeneous, and range from around the figure in their referenced paper of 25% [2][3][4][5] to others more in line with our prevalence of 40-60% [6][7][8]. Nevertheless, and this was one of the points we were trying to highlight, interpretation must be cautious, because the definitions of EUGR are different, or applied at different time points, or over populations with different prevalence of IUGR or different gestational ages.…”
mentioning
confidence: 71%
“…According to both the WHO (in 2013) [3] and recently from Professor Neena Modi [4], at least 200 mg/kg/day of maternal milk should be offered when VPN reach full enteral feeding. In a recent publication by our team, in some hospitalized VPN who did not have the expected growth, the quantity of milk was increased to more than 200 mg/kg/day [5]. This "aggressive" nutrition that was implemented during the 40-44 weeks postconceptional age (PCA) with the persistent nasal continuous positive airway pressure (nCPAP) use in unstable VPN contributed to EUGR (<10th centile) 25% for the body weight and 4.6% for the head circumference at discharge [5].…”
mentioning
confidence: 99%